Settlement calculation on high-rise buildings theory and application - Chen, Xiangfu; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
Settlement Calculation on High-Rise Buildings: Theory and Application discusses, for the first time, the latest developments in settlement calculation theory and case studies including analysis and research results for more than thirty high-rise buildings with a height of 100m-420m. Rigorously reviewed, this book provides a number of useful methods and a unique practical perspective on settlement calculation of high-rise buildings. It covers soft soil constitutive model and computation parameters, the theory of soil stress and strain, and new methods of settlement calculation in super long pile and space-varying rigidity group piles, box(raft), pile-box(raft), diaphragm wall-pile-box(raft) and rock foundation on high-rise buildings. This book is a useful design and construction resource for scientists and engineers, as well as for professionals in structural mechanics and geotechnical engineering. Professor Xiangfu Chen is chairman of the Academic Commission of China State Construction Engineering Corporation (CSCEC), chief engineer of China Construction Beijing Design and Research Institute, and a Doctoral Tutor at Tongji University Shanghai.
Introduction -- Practical Models and Parameters for Settlement Calculation of Deep Foundation of Super High-Rise Buildings on Soft Subgrade -- Mechanics in the Study on Deep Foundation Settlement of Super High-Rise Buildings -- Theoretical Analysis of Subgrade Deformation of Deep Foundations of Super High-Rise Buildings -- Settlement Calculation Methods and Case Studies of Box and Raft Foundations of Super High-Rise Buildings -- Research on Settlement Calculation Method of Super-Long Pile Foundation -- New Design Method for Space-Varying Rigidity Pile Group with Equal Settlement -- Settlement Analysis and Case Study of Diaphragm Wall and Friction Pile-Box (Raft) Foundation on Super High-Rise Building -- Settlement Analysis and Case Study on Rock Foundation and Combined Diaphragm Wall-end-Bearing Pile-box (raft) Foundation -- Forecast and Suggestion of Research on Settlement Calculation.
Electronic reproduction.
Keywords: Settlement of structures -- Mathematical models; Electronic books